Enhanced genetic tools for engineering multigene traits into green algae. - Beth A Rasala; Syh-Shiuan Chao; Matthew Pier; Daniel J Barrera; Stephen P Mayfield (PLoS ONE)
Transgenic microalgae have the potential to impact many diverse biotechnological industries including energy, human and animal nutrition, pharmaceuticals, health and beauty, and specialty chemicals. However, major obstacles to sophisticated genetic and metabolic engineering in algae have been the lack of well-characterized transformation vectors to direct engineered gene products to specific subcellular locations, and the inability to robustly express multiple nuclear-encoded transgenes within a single cell. Here we validate a set of genetic tools that enable protein targeting to distinct subcellular locations, and present two complementary methods for multigene engineering in the eukaryotic green microalga Chlamydomonas reinhardtii. The tools described here will enable advanced metabolic and genetic engineering to promote microalgae biotechnology and product commercialization.